Assessment of potentially pathogenic bacteria isolated from mobile phones of preclinical and hospital-based medical students and healthcare workers (Annals of Medical Research, 2026)
Aim: Healthcare-associated infections (HAIs) remain a major global problem, and contaminated personal devices may act as unnoticed vectors. This study aimed to evaluate the bacterial contamination of mobile phones among medical students and healthcare workers in hospital and non-hospital settings.Materials and Methods: A cross-sectional study was conducted between February and March 2024. A total of 203 mobile phones were sampled: 94 from hospital-exposed participants (clinical students and healthcare workers) and 109 from non-hospital-exposed preclinical students. Surface swabs were inoculated into Mueller-Hinton broth, cultured, and isolates were identified using standard microbiological techniques.Results: Among hospital-exposed participants, bacteria were cultivated from 62/94 phones (65.9%), with potentially pathogenic organisms detected in 13.8%. Among these bacteria were Staphylococcus aureus (n=4, none methicillin-resistant), Pseudomonas spp. (n=2), Acinetobacter baumannii (n=2), Enterococcus faecalis (n=1), Stenotrophomonas maltophilia (n=1), and Bacillus spp. (n=3). Commensals such as Staphylococcus epidermidis (n=36) and Staphylococcus haemolyticus (n=7) predominated. In contrast, only 28/109 samples (25.7%) from preclinical students showed growth, limited to skin flora without pathogenic isolates. The contamination rate was significantly higher in the hospital-exposed group (p
Keywords: Mobile phone contamination; Nosocomial infections; Hand hygiene; Healthcare workers; Medical students; Bacterial colonization